Inspirasi Tulip dengan Penerapan Bunga 3D pada Busana Pesta - Alhabsyi, Chodijah; Suhartini, Ratna (UNIVERSITAS SERAMBI MEKKAH, 2025)
The aim of the research is to find out the results of applying 3D flower manipulation to party clothing inspired by tulips. This research method uses the double diamond method which consists of 4 stages: Discover, Define, Develop, Deliver. The materials used are tile cloth and duces cloth for the main material and manipulating material. Inspired by the tulip flower which has the meaning of hope and cheerfulness, and inspired by the detailed silhouette of the tulip flower shape which is applied as a 3D flower manipulation. The process of applying tulip flower manipulation begins with making a collage, after that creating designs for party clothes and men's suits using the technique of manipulating 3D flowers on clothing. This fast clothing uses an A silhouette and has a tail at the back. The application of manipulating 3D tulips is on the front of the woman's dress and the back of the tail. Meanwhile, the manipulating on the jacket is placed at the top of the jacket pocket as a decorative detail. The results of this research are in the form of a collection of dresses and jackets inspired by tulips which will be displayed at the Unesa fashion design copyright show.